Loss of T-Cell Multifunctionality and TCR-Vβ Repertoire Against Epstein-Barr Virus Is Associated With Worse Prognosis and Clinical Parameters in HIV+ Patients - Hernández, Diana M.; Valderrama, Sandra; Gualtero, Sandra; Hernández, Catalina; López, Marcos; Herrera, Maria Victoria; Solano, Julio; Fiorentino, Susana; Quijano, Sandra (Frontiers in Immunology, 2018)
Epstein - Barr virus (EBV) is an oncogenic virus associated with development of aggressive and poor prognosis B-cell lymphomas in patients carrying Human Immunodeficiency Virus (HIV+ patients). The most important risk factors for these malignancies include immune dysfunction, chronic immune activation, and loss of T-cell receptor (TCR) repertoire. The reunion of all these factors can favor reactivation of EBV, malignant cell transformation, and clinical progression towards B-cell lymphomas. The overarching aim of this study was to evaluate the frequency, phenotype, functionality, and distribution of TCR clonotypes for EBV-specific T-cell subpopulations in HIV+ patients at different clinical stages and HIV+ patients with B-cell lymphoma, and to establish their association with clinical variables of prognostic value. Factors were studied in 56 HIV+ patients at different clinical stages and six HIV+ subjects with diagnosed B-cell lymphoma. We found, a significant decrease in all subpopulations of EBV-specific CD4+ T cells from HIV+ patients at stage 3 and with B-cell lymphoma. EBV-specific effector CD8+ T cells, particularly effector memory cells, were also reduced in HIV+ patients with B-cell lymphoma. Interestingly, in these cells were unable to produce IFN-g and lacked multifunctionality in HIV+ patients. The TCR-VB repertoire, which is key for the protection against EBV in healthy individuals, was less diverse in HIV+ patients, due to a lower frequency of TCR-Vb2+, Vb4+, Vb7.1+, Vb9+, Vb13.6+, Vb14+, Vb17+, Vb22+ CD4+, Vb14+ and, Vb17+ CD8+ T cells. HIV+ patients with positive plasma EBV loads (EBV+HIV+) had a noteworthy decrease in both TNF-a+ and multifunctional TNF-a+/IL-2+ and TNF-a+/IFN-g+ CD8+ T cells. Altogether, our findings demonstrate that HIV+ patients have significant alterations in the immune response to EBV (poor-quality immunity) that can favor viral reactivation, snowballing the risk for developing EBV-associated B-cell lymphomas.